The biology of Geosmithia morbida and susceptibility of walnut and hickory species to thousand cankers disease - Utley, Curtis, author; Tisserat, Ned, advisor; Cranshaw, Whitney, advisor; Jacobi, William, committee member; Klett, James, committee member (Colorado State University. Libraries, 2013)
Since 2001 widespread mortality of black walnut (Juglans nigra) has been reported in Colorado, USA. Affected trees initially show a yellowing and thinning of leaves in the upper crown, followed by twig and branch dieback and ultimately tree death. We report that this mortality is the result of a combination of an expanded geographic range of the walnut twig beetle (Pityophthorus juglandis), its aggressive feeding behavior on black walnut, and extensive cankering caused by a filamentous ascomycete in the genus Geosmithia (Ascomycota: Hypocreales). Thirty seven Geosmithia strains collected from J. californica, J. hindsii, J. major, and J. nigra in eight USA states (AZ, CA, CO, ID, OR, UT, WA) were compared using morphological and molecular methods (ITS rDNA sequences). Strains had common characteristics including a yellowish color of conidia en masse, growth at 37°C, and absence of growth on Czapek-Dox agar and belonged to a single species described here as G. morbida. G. morbida is the first Geosmithia species documented as a plant pathogen. We also tested the susceptibility of hickory and walnut species to G. morbida in greenhouse and field studies. Carya illinoinensis, C. aquatica, and C. ovata were immune. All walnut species tested, including J. ailantifolia, J. californica, J. cinerea, J. hindsii, J. major, J. mandshurica, J. microcarpa, J. nigra and J. regia developed cankers following inoculation with G. morbida. J. nigra had the largest cankers, whereas J. major, a native host of the WTB and presumably G. morbida, had smaller and more superficial cankers. Canker size differed among maternal half-sibling families of J. nigra and J. cinerea, indicating genetic variability in resistance to G. morbida. Our inoculation studies with G. morbida have corroborated many of the field observations on susceptibility of hickory and walnut species to TCD, although the ability of the WTB to successfully attack and breed in walnuts is also an important component in TCD resistance.
Keywords: black walnut; Geosmithia morbida; thousand cankers disease; walnut twig beetle; Carya; Juglans